2016
DOI: 10.1093/gerona/glv307
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Attenuates Age-associated Changes in Tibialis Anterior Tendon Viscoelastic Properties

Abstract: Rapamycin extends mouse life span, but the extent to which rapamycin prevents aging-associated changes in specific tissues remains unclear. Stiffness increases and collagen turnover decreases in mouse tendon with aging; thus, our aim was to determine the effect of long-term rapamycin treatment on the mechanical and structural properties of tendons from old mice. Tendons were harvested from female UM-HET3 mice maintained on a standard chow diet for 4 (adult) or 22 (old) months or fed chow containing polymer-enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…Our results agree with previous animal and clinical studies which reported an increase in tendon compliance with increasing age, which may lead to subsequent injury (Cury et al, 2016; Dudhia et al, 2007; Joseph et al, 2014; Mian et al, 2007; Slane and Thelen, 2015; Svensson et al, 2016). It is important to note that these effects may vary across different tendons, as others have reported age-specific increases in the stiffness and modulus of the tibialis anterior tendon, for example (Slane et al, 2015; Wood et al, 2011; Zaseck et al, 2016). We did not identify any age-related differences in tendon viscoelastic properties, although such differences appear to be present in the entire Achilles tendon-muscle unit in vivo (Plate et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results agree with previous animal and clinical studies which reported an increase in tendon compliance with increasing age, which may lead to subsequent injury (Cury et al, 2016; Dudhia et al, 2007; Joseph et al, 2014; Mian et al, 2007; Slane and Thelen, 2015; Svensson et al, 2016). It is important to note that these effects may vary across different tendons, as others have reported age-specific increases in the stiffness and modulus of the tibialis anterior tendon, for example (Slane et al, 2015; Wood et al, 2011; Zaseck et al, 2016). We did not identify any age-related differences in tendon viscoelastic properties, although such differences appear to be present in the entire Achilles tendon-muscle unit in vivo (Plate et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have reported changes in mRNA levels and activity of proteins involved extracellular matrix organization and turnover that could compromise the structural integrity of aged tendon (Thorpe et al, 2016; Yu et al, 2013; Zaseck et al, 2016). However, results from our HFUS analysis suggest that these distinct molecular profiles do not necessarily translate into macroscale age-specific differences in tendon matrix alignment or density.…”
Section: Discussionmentioning
confidence: 99%
“…The multicentre Intervention Testing Program (ITP), which is supported by the National Institute for Ageing, has identified five drugs that reproducibly increase lifespan in genetically heterogenous mice 147 , including rapamycin, acarbose, nordihydroguaiaretic acid, 17-α-oestradiol and aspirin 147 . Some of these drugs also improve healthspan measures in some tissues of animal models [148][149][150] . Drugs found in other studies to extend rodent lifespan include metformin 151 (although it did not repeat in the ITP at the same dose), drugs targeting the angiotensin-converting enzyme and the aldosterone receptor, and the sirtuin activators SRT2104 152 and SRT1720 153 .…”
Section: Drugs Undergoing Clinical Trialsmentioning
confidence: 99%
“…Importantly, loss of either Tsc1 or Tsc2 leads to activation of mTORC1 signaling 28 , and this approach has been used to show the role of mTORC1 signaling in bone and cartilage development 29 , 30 . In the context of the tendon, recent studies showed that rapamycin, an inhibitor of mTORC1 activity, can attenuate age-associated changes in tendons 31 , 32 . However, the specific role of mTORC1 signaling in tendon development and homeostasis is not known.…”
Section: Introductionmentioning
confidence: 99%